Business Model Canvas as diagnostic tool of the creation of cultural value: Conceptual and exploratory approach to the case of Ferreira’s de Castro Cultural Complex - Tavares, S. A.; Ferreira, P. A. (2020 15th Iberian Conference on Information Systems and Technologies (CISTI), 2020)
The definitions and concepts associated to business model are changing because the economic and financial transactions caused by the digital era. Those could be understood as the entrepreneur and manager conceptual tool that helps the decision making, root to create and deliver economic, non-economic value and/or economic impact, social, environmental, cultural, among others, this one as measures of that. The article purpose is exploring the business model canvas as diagnostic tool in the process of creation and presentation of cultural value to the community, being the study object Ferreira’s de Castro Cultural Complex. It’s a case study, hybrid – theoretic-conceptual and empirical – and exploratory. Was followed a qualitative methodology with a constructivist paradigm and an interpretative base. The data were collected through a documental analysis and semi-structured recorded interviews and for the data analysis were used content analyse. Between others, concludes that: (a) the business model canvas is a useful and adaptable tool to diagnose the system of creation, development, renovation and dissemination of cultural value and (b) the complex presents some frailties like the incapacity of looking to communication as generator and spreading cultural value factor and the consequent effects of that. Was possible realize theoretic-conceptual solutions for the debilities, those are practicable. This study contributes to the practice, could be replicated to other similar cases. Is relevant to the investigation because turn possible the creation of hypothesis for later tests in study deepening or in future study cases. In function of the literature review, this study is the first to explore the BMC as diagnostic tool at value creation by cultural equipment’s.